Analysis Quality of Service Wireless LAN at University PGRI Yogyakarta - Nur Kukuh Wicaksono; Bambang Sugiantoro (IJID (International Journal on Informatics for Development), 2017)
PGRI University of Yogyakarta is an educational institution that uses the internet as one of the supporting facilities and infrastructures to manage and organize the data and information used by the student to find references about the lecture. PGRI University Yogyakarta has three buildings on the main campus building A building B and C buildings, where each building using wireless LAN as a means for students to use the internet network, the weakness of the wireless LAN network where poor internet network in the wireless LAN network. Thus the researchers wanted to analyze the Quality of Service wireless LAN networks in building A, building B, and C buildings, in each floor.With the existence of quality of the network at PGRI University of Yogyakarta will be done by interviews and observation methods, problems that occur in wireless LAN networks in each building have been prepared in advance, after which it will do an analysis of wireless LAN networks using quality of service parameters, namely delay, packet loss, bandwidth, throughput and factors that influence the wireless network at the University of PGRI Yogyakarta.The results of the measurement and monitoring of Quality of Service wireless LAN at PGRI University of Yogyakarta in building A, building B, C on each floor of the building can be classified in the category of poor with the average delay for each building to around 150 ms and packet loss = 28%, bandwidth = 173523 bits / s and throughput = 22%, and the factors that occurred in the signal range cannot cover every room in every building. From these results it can be concluded that the quality of the wireless LAN at the University PGRI Yogyakarta according to the TIPHON standards categorized as poor.